Configuring parents as citizens and consumers: local variations in informational material about school allocation and choice in Sweden - Hanna Sjögren; Baki Cakici (Education Inquiry)
In this paper, we shed light on the mundane performance of market-logics in public educational settings by focusing on municipality websites in Skåne County, Sweden, that inform parents about local school choice policies and procedures. We build on existing knowledge about the importance of websites in school choice systems. The aim of the paper is to 1) identify different ways in which Swedish municipalities configure parents in local school choice settings and 2) relate these configurations of parents to different ideas about the purpose of education. We draw on theoretical insights from Science and Technology Studies (STS) on how technical systems shape their own (future) users as well as the theoretical conceptualisation of education as a private and public good. Our data derives from 27 municipalities in the Skåne County in southern Sweden. We identify two types of scripts in the data; one that expects parents to make a choice and one that does not expect such a choice from the parents. In conclusion, our study indicates that children and their families in Sweden might encounter different understandings of the aims and responsibilities related to education, depending on which municipality they live in.